PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Elvandri Yogi Pratama; Joko Sutrisno AB; Nurashri Partasiwi (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2022)
This research is a quasi-experimental research which aims to determine the effect of the Think Pair Share cooperative learning model on students' mathematical communication skills. This research was conducted in the even semester of the 2021/2022 academic year. Sampling was done by purposive random sampling, it was found that class VIIA was the experimental class and class VIIB was the conventional class. The instrument used in this study was an essay question to measure students' mathematical communication skills. Before the instrument test is used, the validity, reliability, level of difficulty and also the discriminatory power of the questions are tested. Hypothesis testing was carried out using the t-test because it met the requirements for the data to be normally distributed and homogeneous. Based on the results of research and discussion, it can be concluded that the cooperative learning model of the Think Pair Share type affects the communication skills of students.